Harnessing nature’s pharmacy: investigating natural compounds as novel therapeutics for ulcerative colitis - Huang, You; Wu, Qiuhong; Li, Sha; Lin, Xia; Yang, Shasha; Zhu, Rui; Fu, Chaomei; Zhang, Zhen (Frontiers in Pharmacology, 2024)
Backgrounds: Ulcerative colitis (UC) is a form of chronic inflammatory bowel disease, and UC diagnosis rates continue to rise throughout the globe. The research and development of new drugs for the treatment of UC are urgent, and natural compounds are an important source. However, there is a lack of systematic summarization of natural compounds and their mechanisms for the treatment of UC. Methods: To fill these gaps, we consulted the papers in the databases below from their inception until July 2023: Web of Science, PubMed, China National Knowledge Infrastructure, and Wanfang Data, to obtain information on the relationship between natural compounds and UC. Results: The results showed that 279 natural compounds treat UC through four main mechanisms, including, including regulating gut microbiota and metabolites (Mechanism I), protecting the intestinal mucosal barrier (Mechanism II), regulating intestinal mucosal immune response (Mechanism III), as well as the other mechanisms (Mechanism Ⅳ) such as cellular autophagy modulation and ferroptosis inhibition. Of these, Mechanism III is regulated by all natural compounds. The 279 natural compounds, including 62 terpenoids, 57 alkaloids, 52 flavonoids, 26 phenols, 19 phenylpropanoids, 9 steroids, 9 saponins, 8 quinonoids, 6 vitamins, and 31 others, can effectively ameliorate UC. Of these, terpenoids, alkaloids, and flavonoids have the greatest potential for treating UC. It is noteworthy to highlight that a total of 54 natural compounds exhibit their therapeutic effects by modulating Mechanisms I, II, and III.Conclusions: This review serves as a comprehensive resource for the pharmaceutical industry, researchers, and clinicians seeking novel therapeutic approaches to combat UC. Harnessing the therapeutic potential of these natural compounds may significantly contribute to the improvement of the quality of life of patients with UC and promotion of disease-modifying therapies in the future.